PERANCANGAN SISTEM INFORMASI PEMASARAN KERAJINAN TANGAN KHAS INHIL BERBASIS WEB - Bayu Rianto (RJOCS (Riau Journal of Computer Science), 2018)
Marketing is one of the factors that play an important role in determining the success of an attempt tointroduce the types of products offered. The more creative the marketing will be more and more consumers areinterested. One form of creative marketing by using a web-based information system with a unique andattractive appearance. Currently, the development and advancement of the internet is also very fast, either inperson or agency is in need of internet. They use the internet to present the latest information services requiredby the community. An agency or company is in need of internet services. As in Dekranasda Kab. Inhil, theydesperately need promotion services to market the production is widespread, but during this promotion are stillusing manual systems only. Therefore, in this study will raise the issue of web-based marketing informationsystem to facilitate the marketing and sale of goods production Dekranasda. Web-based Marketing InformationSystem using PHP programming language designed using Dreamweaver 8 application and the MySQLdatabase. As well as the Mozilla Firefox application used to display web-based marketing information systemthat has been designed. Hopefully with this system can facilitate the promotion and sale of handicrafts Inhil andits products can be recognized by the public.